Innovation in Distribution of Wealth Through Zakat: Building Shared Prosperity by Applying Tafsir Qs. At-Taubah Verse 60 - Uswatun Hasanah; Harisah Harisah; Mohammad Ali Al Humaidy (Al-Hiwalah: Journal of Sharia Economic Law, 2024)
Whether it is recognized or not, there are many things in society problems related to the economy,especially not equal distribution of income between one group and another others that cause social and economic disparities.To overcome this problem, zakat is the obligation of every Muslim for those who have fulfilled the requirements to accomplish this, become an alternative solution for overcome this problem. In this case distribution Zakat funds are the most important part of building shared prosperity. But in this era of globalization of course. The distribution of zakat requires new innovations through application of QS interpretation. at-taubah verse 60 effectively, efficiently and relevant to the development of the times by doing various collaborations and modern distribution models. Tree The discussion in this article is the application of QS interpretation. At-Taubah verse 60 which emphasizes the concept of caring, justice and economic equality by combining new innovations to create a more effective system in building economic prosperity, of course can be realized by applying eight groups mustahiq who has the right to receive and utilize funds zakat.